Duration of Exposure to General Endotracheal Anesthesia during Cesarean Deliveries at Term and Perinatal Complications - Swanson, Kate; Liang, Luzhou; Grobman, William A.; Higgins, Nicole; Roy, Archana; Son, Moeun (American Journal of Perinatology, 2021)
Objective To examine whether the duration of time from initiation of general endotracheal anesthesia (GETA) to delivery for cesarean deliveries (CDs) performed is related to perinatal outcomes.Study Design This is a retrospective study of patients with singleton nonanomalous gestations undergoing CD ≥37 weeks of gestation under GETA with reassuring fetal status at a single tertiary care center from 2000 to 2016. Duration from GETA initiation until delivery was calculated as the time interval from GETA induction to delivery (I-D), categorized into tertiles. Outcomes for those in the tertile with the shortest I-D were compared with those in the other two tertiles. The primary perinatal outcome was a composite of complications (continuous positive airway pressure or high-flow nasal cannula for ≥2 consecutive hours, inspired oxygen ≥30% for ≥4 consecutive hours, mechanical ventilation, stillbirth, or neonatal death ≤72 hours after birth). Secondary outcomes were 5-minute Apgar score <7 and a composite of maternal morbidity (bladder injury, bowel injury, and extension of hysterotomy). Bivariable and multivariable analyses were used to compare outcomes.Results Two hundred eighteen maternal–perinatal dyads were analyzed. They were dichotomized based on I-D ≤4 minutes (those in the tertile with the shortest duration) or >4 minutes. Women with I-D >4 minutes were more likely to have prior abdominal surgery and less likely to have labored prior to CD. I-D >4 minutes was associated with significantly increased frequency of the primary perinatal outcome. This persisted after multivariable adjustment. In bivariable analysis, 5-minute Apgar <7 was more common in the group with I-D >4 minutes, but this did not persist in multivariable analysis. Frequency of maternal morbidity did not differ.Conclusion When CD is performed at term using GETA without evidence of nonreassuring fetal status prior to delivery, I-D interval >4 minutes is associated with increased frequency of perinatal complications.Key Points
Keywords: general anesthesia; cesarean delivery; neonatal respiratory complications